2019
DOI: 10.1038/s41598-019-55200-z
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent circuit parameters of planar transmission lines with spoof surface plasmon polaritons and its application in high density circuits

Abstract: In this paper, the characteristics of a class of transmission lines which support spoof surface plasmon polaritons are investigated both numerically and experimentally. In order to provide the characteristic impedance of spoof surface plasmon polaritons for PCB designers, the equivalent circuit parameters of the microstrip line periodically structured on subwavelength scale are extracted with the numerical method. It is found that the equivalent circuit parameters significantly vary with frequency when the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In order to calculate the characteristic impedance modulus , one can be referred to the method provided in Refs. 15 , 16 , where the capacitance and inductance of the unit length of the periodic microstrip lines can be extracted from the Maxwell equations. The numerical result of the capacitance and inductance per unit length of the SPMLs selected in this paper is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to calculate the characteristic impedance modulus , one can be referred to the method provided in Refs. 15 , 16 , where the capacitance and inductance of the unit length of the periodic microstrip lines can be extracted from the Maxwell equations. The numerical result of the capacitance and inductance per unit length of the SPMLs selected in this paper is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( 4 ). To enable the circuit model to provide an accurate S -parameters calculation result, the resistance value of metallic conductors in the microstrip line can be obtained by the perturbation method 15 and the conductance can be calculated by using the relevant equations given in Ref. 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The circuit parameters of the periodic microstrip line are extracted under the quasi-static approximation [30,31]. In addition, in the literature, some references [32][33][34] and microwave engineering standard textbooks [26,27] also provided the methods for calculating the equivalent circuit parameters of transmission lines.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…[39] 0.04-0.12 THz <−10 dB ∼−1.5dB From Table 3, it can be observed that most of the previous researchers have worked with SSPP interconnects operating in the gigahertz range. For example, 2-14 GHz, 0-10 GHz, 6-11 GHz and 46.1-73.7 GHz are the simulated frequencies found in [18,30,32,33], respectively. However, the existing electrical connectors show fairly good performance in the gigahertz frequency.…”
Section: Performance Summary and Comparisonmentioning
confidence: 99%